2005
DOI: 10.1242/jeb.01532
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial changes in the expression pattern of multiple red and green subtype opsin genes during zebrafish development

Abstract: SUMMARY Zebrafish have two red, LWS-1 and LWS-2, and four green, RH2-1, RH2-2, RH2-3 and RH2-4, opsin genes encoding photopigments with distinct absorption spectra. Occurrence of opsin subtypes by gene duplication is characteristic of fish but little is known whether the subtypes are expressed differently in the retina, either spatially or temporally. Here we show by in situ hybridization the dynamic expression patterns of the opsin subtypes in the zebrafish retina. Expression of red type opsins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
189
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(209 citation statements)
references
References 22 publications
19
189
0
1
Order By: Relevance
“…Previous studies demonstrated that the expression pattern of fish opsins might be regulated spatially, as well as temporally, in the retina (31)(32)(33). In the case of zebrafish, shorter-wavelength RH2 proteins are first expressed in the central part of the retina, whereas longer wavelength proteins are expressed later in the peripheral part (34). Similarly, the five RH2 genes of tuna might be differentially expressed in retina, which would contribute to the visual diversification of tuna.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that the expression pattern of fish opsins might be regulated spatially, as well as temporally, in the retina (31)(32)(33). In the case of zebrafish, shorter-wavelength RH2 proteins are first expressed in the central part of the retina, whereas longer wavelength proteins are expressed later in the peripheral part (34). Similarly, the five RH2 genes of tuna might be differentially expressed in retina, which would contribute to the visual diversification of tuna.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that LWS S180r is expressed in more cone cells or in a different region of the retina at a different life history stage, as only adults were surveyed in this study. Opsin gene expression and regional cone abundance vary during ontogeny in a diversity of fish including cichlids , winter flounder (Mader and Cameron, 2004), salmonids and zebrafish (Takechi and Kawamura, 2005;Allison et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…intra-retinal variation) could be advantageous for fish, given that the light hitting the dorsal retina is of different spectral composition from that hitting the ventral retina, as a result of the filtering properties of water and any dissolved organic solutes or suspended particulates in it that alter the spectral properties of light. Several species of fish have been shown to possess intra-retinal variation in spectral sensitivity, exhibiting different densities and/or distributions of various photoreceptor types, apparently to deal with varied visual tasks (Takechi and Kawamura, 2005;Allison et al, 2006;Veldhoen et al, 2006;Temple et al, 2010;Temple, 2011). This intra-retinal variation in opsin gene expression may also influence the behaviour of species that use colour in mate choice decisions (Temple, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Green cones (40-45 hpf) Chinen et al (2003), Takechi and Kawamura (2005), Vihtelic et al (1999) NDRG1 RNA probe…”
Section: Rna Probesmentioning
confidence: 99%
“…Red cones (40-45 hpf) Chinen et al (2003), Raymond et al (1995), Takechi and Kawamura (2005) Rod opsin Ab (poly) Rods (≤3 dpf) Doerre and Malicki (2001), Vihtelic et al (1999) Rod opsin c…”
Section: Rna Probesmentioning
confidence: 99%